Evaluation on the perceived benefits and obstacles of technology implementation and the role of organizational culture: evidences from Malaysian SMEs - Abd Rahman, Azmawani; Ng, Siew Imm; Sambasivan, Murali; Shahron, Syairah Aimi (2012)
Technological innovations are changing rapidly and firms have to continuously update their operation technologies to ensure sustainability and competitiveness. However, new technology adoption is a risky endeavour which may seriously endanger the long-term profitability of the firms. Therefore, technology adoption continues to be an important research agenda as many firms are still struggling with the implementation issues. This study investigates why firms do not adopt new manufacturing technology although they have the intention to adopt. Specifically, it focuses on the influence of organizational culture on the perceived benefits and obstacles of technology implementation. Based on survey results of 140 SMEs, this study found that financial constraint and lack of knowledge as the top two perceived obstacles of technology adoption. Meanwhile, competitive benefits were found as a major driver for their intention to have the technology. Although organizational culture was found to have no influence on perceived benefits of technology adoption, firms with different culture differ in terms of ways in which they perceived obstacles to technology adoption. It was found that group culture is less likely to perceive people resistance as obstacles to technology adoption. This study helps to address issues related to the importance of having the right organizational culture within the context of technology adoption. The results of the study can serve as guidelines to the practitioner and the policy makers.